022 PP: RESEARCH DESIGN BOUNDARIES FOR QUALITATIVE RESEARCH, STAKEHOLDER AND PATIENT AND PUBLIC INVOLVEMENT, AND WHY THEY MATTER. (3rd March 2017) - Keenan, J; Poland, F; Wilson, P; Mathie, E; Boote, J; Varley, A; Wythe, H; Wellings, A; Vicary, P; Cowe, M; Munday, D; Howe, A
Abstract : Within current mainstream understandings of patient and public involvement (PPI) in health research, a clear distinction is made between what 'involvement' in research is: 'research being carried out 'with' or 'by' members of the public rather than 'to', 'about' or 'for' them'1 and what it is not: namely 'engagement with' and 'participation in' research. Research evidence describes problems than can arise when such distinctions are unclear or misunderstood (often by those new or unfamiliar with PPI); or when distinctions are intentionally blurred e.g. by 'dual roles' being created within some projects, where research participants also advise on the conduct of projects. What is less widely examined, however, is the blurring of boundaries between the object of enquiry which is the business of PPI for that project, the data which is the object of qualitative collection involving discussion with participants and the purposeful research activities which are best progressed through engagement with stakeholders. This poster draws upon case study findings from two recent, similar National Institute for Health Research (NIHR)-funded evaluations of PPI in health research: RAPPORT (England-wide) and IMPRESS (regional research programme-specific), pertaining to how researchers (from various disciplines, using various research designs) within different case study research projects can blur the boundaries between qualitative research, stakeholder events and PPI. We pose questions pertaining to the consequences of blurred research design boundaries for the success of outcomes of public-research collaborations. We query why, and to what extent, such distinctions matter in co-producing knowledge and in measuring the impact of various investments in collaborative research activities.